Komunikasi Orang Tua dan Tingkat Kecanduan Gawai Anak Usia Dini Selama Pandemi Covid-19 - Ahmad Khairul Nuzuli Ahmad Khairul Nuzuli (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2021)
Since the outbreak of the Covid-19 pandemic, children spend more time at home and use smartphones in their spare time. Excessive use of gadgets is bad for children physically and psychologically. Parents as a reference group have a function in influencing and controlling children in using gadgets. This study aims to confirm the effect of the intensity of parent-child communication on the level of addiction to playing gadgets for early childhood during the Covid-19 pandemic. Collecting data using a Likert scale questionnaire. The instrument was developed by the researcher himself using the intensity of parental communication and addiction to playing gadgets. The instrument was tested for validity and reliability. The data analysis technique was carried out through simple regression analysis with the help of the Statistical Product and Service Solution (SPSS). The results of the study show the results of 0.002, this number is smaller than 0.05, indicating that there is a significant effect between the two variables. Regression test shows that the lower the communication between parents and children, the higher the child's addiction to gadgets.